Efektivitas Game Edukasi Berbasis Android Berbantuan Website Wordwall Pada Mata Pelajaran Sejarah - Muhammad Reza Pahlevi; Vionita Apriliyani (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to determine the effectiveness of using android-based educational games assisted by the Wordwall website in history subjects. This research is a development research using direct observation techniques and distributing questionnaires to the research location. The method used is research and development (RnD) developed with the Alessi & Trollip model which consists of three stages, namely 1) Planning, 2) Design, 3) Development. The research subjects were 11th grade students of Srijaya Negara High School Palembang. The results obtained in the form of pretests and posttests to measure the level of student success in participating in history learning. Field test results showed an increase in learning outcomes before and after using educational games by 45.3% with an N-gain of 0.71 in the high category. These results indicate that the effectiveness of the development of android-based educational games assisted by the wordwall website is effective in increasing the learning motivation of high school students in history subjects.